Do emotional labour strategies influence emotional exhaustion and professional identity or vice versa? Evidence from new nurses. (4th December 2019) - Liu, Han; Zou, Hao‐Yun; Wang, Hai‐Jiang; Xu, Xiaohong; Liao, Jian‐Qiao
Abstract: Aims: The aim was to examine the reciprocal relationships of emotional labour strategies with emotional exhaustion and professional identity. Design: This study adopted a four‐wave cross‐lagged panel design. Methods: Survey data were collected in 2018 from a sample of 171 newly hired nurses from 58 hospitals in 11 provinces of China. Nurses' emotional labour (i.e., deep acting and surface acting), emotional exhaustion and professional identity were repeatedly measured. Cross‐lagged panel analyses were conducted to examine the reciprocal relationships we hypothesized. Results: We found that emotional exhaustion was positively related to surface acting (but not vice versa); deep acting was negatively related to emotional exhaustion (but not vice versa); professional identity was positively related to deep acting (but not vice versa). Conclusion: Our findings suggest that deep acting and professional identity may decrease the level of emotional exhaustion, whereas emotionally exhausted nurses are more likely to employ surface acting strategies. Impact: This research finding will have an impact on the nursing management. Healthcare managers may consider workshops or training and development programs that promote nurses' professional identify to promote nurses' use of deep acting and consequently reduce their level of emotional exhaustion, which has been associated with a variety of negative consequences, such as low quality of patient service, high medical accidents, and turnover rate. Abstract : 目的: 研究情绪劳动策略与情绪枯竭和职业认同的相互关系。 设计: 本研究采用四波交叉滞后组设计。 方法: 2018年, 对我国11个省份58家医院的171名新聘护士进行问卷调查, 收集数据。反复测量护士的情绪劳动(即深层伪装和表层伪装)、情绪枯竭和职业认同。采用交叉滞后组分析来检验我们先前假设的相互关系。 结果: 我们发现, 情绪枯竭与表层伪装呈显著正相关(反之不成立);深层伪装与情绪枯竭呈显著负相关(反之不成立);职业认同与深层伪装呈显著正相关(反之不成立)。 结论: 我们的研究结果表明, 深层伪装和职业认同可能会降低情绪枯竭的程度, 而面临情绪枯竭的护士更有可能采用表层伪装策略。 影响: 本项研究发现将对护理管理工作产生影响。医疗保健管理人员可能会考虑举办研讨会或开展培训和发展计划, 以提高护士的职业认同感, 从而促进护士采用深层伪装策略, 降低他们的情绪枯竭程度。同时情绪枯竭还与各种负面影响有关, 如患者服务质量低, 医疗事故频发, 人员流动率高。